Hydroelectric Power: Balancing Renewable Energy Production with Aquatic Ecosystem Health - Ojong Felix Enow; Andrew Tochukwu Ofoedu; Ebimor Yinka Gbabo; Possible Emeka Chima; Oluwapelumi Joseph Adebowale (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Hydroelectric power stands as a significant pillar in the global pursuit of renewable energy sources, yet its development and operation necessitate a delicate balance between energy production and the preservation of aquatic ecosystem health. This review delves into the intricate relationship between hydroelectricity generation and the ecological integrity of freshwater environments. The utilization of flowing water to generate electricity offers immense potential for sustainable energy production, contributing to mitigating climate change and reducing dependence on fossil fuels. However, the construction of dams and reservoirs for hydroelectric projects can have profound ecological impacts, altering river flow patterns, fragmenting habitats, and disrupting aquatic biodiversity. These alterations can lead to adverse consequences such as habitat degradation, species displacement, and changes in water quality. Effective management strategies are imperative to minimize the environmental footprint of hydroelectric facilities and safeguard aquatic ecosystems. Integrated approaches incorporating comprehensive environmental impact assessments, adaptive management practices, and stakeholder engagement are essential for sustainable hydroelectric development. Additionally, the implementation of fish passage technologies, sediment management measures, and environmental flow regimes can help mitigate the adverse effects on aquatic fauna and flora. Furthermore, advancements in turbine design and operational practices offer opportunities to enhance the compatibility of hydroelectricity generation with aquatic ecosystem health. By optimizing turbine configurations and scheduling releases, it is possible to mitigate downstream flow alterations and minimize adverse impacts on migratory fish populations. The pursuit of hydroelectric power as a renewable energy source must be accompanied by a steadfast commitment to ecological stewardship. By integrating environmental considerations into the planning, design, and operation of hydroelectric projects, it is feasible to strike a balance between renewable energy production and the preservation of aquatic ecosystem integrity.